The effect of narcotics on ferroptosis-related molecular mechanisms and signalling pathways - Zeng, Xiaoqin; Li, Jingda; Yang, Fuyuan; Xia, Rui (Frontiers in Pharmacology, 2022)
Ferroptosis is a novel programmed cell death form characterized by iron-mediated reactive oxygen species-induced lipid peroxidation and subsequent cell damage that is distinct from apoptosis, necroptosis, pyroptosis, and autophagy. Most studies on ferroptosis are based on its function and mechanism, but there have been relatively few studies on the effects of drugs, especially anaesthetics, on ferroptosis. Therefore, we summarized the literature on the effects of anaesthetics on ferroptosis in recent years to understand the underlying mechanism. In particular, we focused on the targets of various anaesthetics in different mechanisms of ferroptosis. The aims of this review are to provide a relatively reasonable drug regimen for clinicians, to explore potential ferroptosis protection drugs and targets, to reduce perioperative complications, and to improve the postoperative performance of patients, especially those who are critically ill.